(untitled) (Educational Knowledge, 2024)
The methodologies and tools employed in the pedagogical realm wield a profound influence on the academic prowess of students. Within this scholarly context, this inquiry scrutinizes the pivotal role and consequential impacts that information and communication technologies (ICTs) may exert on the scholastic achievements of students. The methodological approach undertaken aligns with a quantitative, descriptive paradigm, employing a non-experimental design. Data collection transpired through the implementation of a questionnaire, leveraging the Likert Scale, disseminated among 30 educators situated at Basic School No. 1717 Mariscal Francisco Solano López – Tacuara, situated in the Republic of Paraguay. The discerned outcomes illuminate a discernible inclination towards the incorporation of technologies and their application in students’ learning processes, specifically through activities focalized on digital content. This discernible trend is causatively linked to a positive modulation in the academic performance exhibited by the student cohort.